Outcomes of One-Stage Surgical Repair for Berry Syndrome in Neonates - Shi, Xu-Cong; Weng, Jian-Bin; Yu, Jin; Ma, Xiao-Hui; Pu, Yi-Qing; Ying, Li-Yang; Yu, Jian-Gen (Frontiers in Cardiovascular Medicine, 2022)
Background: Berry syndrome is a challenging disease for surgeons to make early diagnosis and successful surgical correction in the neonatal period. Here we summarized the clinical features of three neonates with berry syndrome in our center to optimize the therapeutic effect in the future. Methods: From January 2014 to December 2019, three neonates with berry syndrome underwent one-stage surgical repair in our center. We mainly used two different surgical techniques to repair it, and collected clinical data retrospectively from hospitalization history, outpatient records and telephone follow-up. Results: The age at operation was 28, 8 and 8 days and the body weight was 3.65, 3.86 and 3.0 kg，respectively. The morphology of interrupted aortic arch was type A in two patients and type B in one patient. The aortopulmonary window morphology was type IIa, III and IIb respectively. The phenotype of interrupted aortic arch type B combined with aortopulmonary window type III in our second patient was reported for the first time so far. All patients survived and were followed up to date. The second patient using intra-aortic bafﬂe experienced twice reoperation for right pulmonary artery stenosis. All patients grew well so far. Conclusion: Once diagnosed in the neonatal period, berry syndrome can be safely corrected by one-stage surgical repair in experienced cardiac centers. Considering the variability of location where the right pulmonary artery arising from the posterior wall of the aorta, it is difficult to find the best surgical method for each patient.